Positive electrode and secondary battery using same

By using the first and second lithium composite oxides with a specific range of Li/Me ratio and crystallite diameter in the positive electrode of the lithium ion secondary battery, the problem of difficulty in balancing high capacity and high output characteristics in the existing technology is solved, The high performance of lithium-ion secondary batteries is achieved.

CN119340339APending Publication Date: 2025-01-21PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410963527.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both high capacity and output characteristics in lithium-ion secondary batteries.

Method used

A cathode active material layer composed of a first lithium composite oxide and a second lithium composite oxide having a layered structure is used. The first lithium composite oxide has a Li/Me ratio of 0.90 to 0.97, and the second lithium composite oxide has a Li/Me ratio of 0.90 to 0.97. The Li/Me ratio is 1.10 to 1.20, and the output characteristics and capacity characteristics of the battery are improved by adjusting the crystallite diameter.

Benefits of technology

The high-capacity and high-output characteristics of lithium-ion secondary batteries are achieved, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340339A_ABST
    Figure CN119340339A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode and a secondary battery using the same. Provided is a positive electrode capable of imparting a high level of capacity characteristics and output characteristics to each of secondary batteries. A positive electrode disclosed herein includes a positive electrode current collector, and a positive electrode active material layer supported by the positive electrode current collector. The positive electrode active material layer contains a first lithium composite oxide having a layered structure and a second lithium composite oxide having a layered structure. In the first lithium composite oxide, the molar ratio of Li to a metal other than Li is 0.90-0.97. In the second lithium composite oxide, the molar ratio of Li to a metal other than Li is 1.10-1.20. The crystallite diameter of the (104) plane of the first lithium composite oxide is # imgabs0 #, and the crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode and a secondary battery using the positive electrode. Background Art

[0002] In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, portable terminals, etc., and as power sources for driving vehicles such as electric vehicles (BEV), hybrid vehicles (HEV), and plug-in hybrid vehicles (PHEV).

[0003] Positive electrodes for secondary batteries such as lithium ion secondary batteries generally use positive electrode active materials. As positive electrode active materials, lithium composite oxides are often used. Patent document 1 discloses that a lithium composite oxide having a Li / Me ratio of less than 1 is combined with a lithium composite oxide having an excess of Li (i.e., a lithium composite oxide having a Li / Me ratio of more than 1) as a positive electrode active material, so that the crystallite diameter of the lithium composite oxide having a Li / Me ratio of less than 1 is greater than 180 nm ( The output characteristics and capacity characteristics of the secondary battery are improved. The Li / Me ratio of the lithium composite oxide is the molar ratio of Li to the metal (Me) other than Li.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application No. 2021-518049 Summary of the invention

[0007] However, as a result of intensive research, the present inventors have newly discovered that the above-mentioned conventional technology has a problem in that both capacity characteristics and output characteristics cannot be achieved at a high level.

[0008] Therefore, an object of the present invention is to provide a positive electrode capable of imparting both high-level capacity characteristics and high-level output characteristics to a secondary battery.

[0009] The positive electrode disclosed herein includes a positive electrode collector and a positive electrode active material layer supported by the positive electrode collector. The positive electrode active material layer contains: a first lithium composite oxide having a layered structure, and a second lithium composite oxide having a layered structure. In the first lithium composite oxide, the molar ratio of Li to metals other than Li is 0.90 to 0.97. In the second lithium composite oxide, the molar ratio of Li to metals other than Li is 1.10 to 1.20. The crystallite diameter of the (104) plane of the first lithium composite oxide is The crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.

[0010] According to such a configuration, it is possible to provide a positive electrode capable of imparting high-level capacity characteristics and output characteristics to a secondary battery.

[0011] From another aspect, the secondary battery disclosed herein includes: the above-mentioned positive electrode, negative electrode, and electrolyte. According to such a configuration, a secondary battery having high capacity characteristics and high output characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a cross-sectional view schematically showing a positive electrode according to one embodiment of the present invention.

[0013] Figure 2 This is a cross-sectional view schematically showing the internal structure of a lithium ion secondary battery according to one embodiment of the present invention.

[0014] Figure 3 This is an exploded schematic diagram showing the structure of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION

[0015] The following describes the embodiments of the present invention with reference to the accompanying drawings. Furthermore, matters not mentioned in this specification, that is, matters required for the implementation of the present invention, can be understood as design matters for those skilled in the art based on the prior art in this field. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, the same figure marks are marked on the components and parts that play the same role for illustration. In addition, the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. It should be noted that A and B are included in the numerical range expressed as "A~B" in this specification.

[0016] It should be noted that in this specification, "secondary battery" refers to a storage device that can be repeatedly charged and discharged. In addition, in this specification, "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as charge carriers and realizes charge and discharge by the movement of charges accompanied by lithium ions between positive and negative electrodes.

[0017] Hereinafter, the present invention will be described in detail by taking a positive electrode used in a lithium ion secondary battery as an example, but the present invention is not intended to be limited to the contents described in this embodiment. Figure 1 It is a schematic cross-sectional view along the thickness direction and the width direction of the positive electrode involved in this embodiment.

[0018] As shown in the figure, the positive electrode 50 includes a positive electrode collector 52 and a positive electrode active material layer 54 supported by the positive electrode collector 52. In the example shown in the figure, the positive electrode active material layer 54 is provided on both sides of the positive electrode collector 52. However, the positive electrode active material layer 54 may be provided on a single side of the positive electrode collector 52. Preferably, the positive electrode active material layer 54 is provided on both sides of the positive electrode collector 52.

[0019] As shown in the example, a positive electrode active material layer non-formed portion 52a where no positive electrode active material layer 54 is provided may be provided at one end portion in the width direction of the positive electrode 50. In the positive electrode active material layer non-formed portion 52a, the positive electrode current collector 52 is exposed, and the positive electrode active material layer non-formed portion 52a can function as a current collecting portion. However, the configuration for collecting current from the positive electrode 50 is not limited to this.

[0020] As the positive electrode current collector 52, a known positive electrode current collector used in lithium ion secondary batteries can be used, and examples thereof include sheets or foils made of metals with good conductivity (for example, aluminum, nickel, titanium, stainless steel, etc.). As the positive electrode current collector 52, aluminum foil is preferred.

[0021] The size of the positive electrode current collector 52 is not particularly limited and can be appropriately determined according to the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, and is, for example, 5 μm to 35 μm, preferably 7 μm to 20 μm.

[0022] The positive electrode active material layer 54 contains a positive electrode active material. In this embodiment, a first lithium composite oxide having a layered structure and a second lithium composite oxide having a layered structure are used together as the positive electrode active material. Therefore, the positive electrode active material layer contains at least the first lithium composite oxide and the second lithium composite oxide. In the following description, when abbreviated as "lithium composite oxide", basically, the description is equivalent to both the first lithium composite oxide and the second lithium composite oxide.

[0023] Examples of the types of lithium composite oxides having a layered structure include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.

[0024] It should be noted that in this specification, the so-called "lithium nickel cobalt manganese composite oxide" is a term that includes oxides containing one or more additional elements other than Li, Ni, Co, Mn, and O in addition to oxides containing these elements. Examples of the additional elements include transition metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn, typical metal elements, and the like. In addition, the additional elements may be semi-metallic elements such as B, C, Si, and P, and non-metallic elements such as S, F, Cl, Br, and I. This is also true for the above-mentioned lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.

[0025] The first lithium composite oxide and the second lithium composite oxide may be the same type of lithium composite oxide or different types of lithium composite oxides.

[0026] When different types of lithium composite oxides are used, it is easy to distinguish the first lithium composite oxide from the second lithium composite oxide.

[0027] When the same type of lithium composite oxide is used, the characteristics of the lithium ion secondary battery 100 can be easily adjusted. When the same type of lithium composite oxide is used, it is preferred that the first lithium composite oxide and the second lithium composite oxide are both lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, and more preferably lithium nickel cobalt manganese composite oxides. In addition, in this specification, the same type of lithium composite oxide means that the constituent elements contained in the lithium composite oxide are the same. Therefore, for example, if the first lithium composite oxide and the second lithium composite oxide are both lithium nickel cobalt manganese composite oxides, even if the element ratio of the constituent elements in the first lithium composite oxide and the second lithium composite oxide is different, they are the same type of lithium composite oxides.

[0028] The positive electrode active material may be composed of only the first lithium composite oxide and the second lithium composite oxide. However, the positive electrode active material layer 54 may contain positive electrode active materials other than the first lithium composite oxide and the second lithium composite oxide within a range that does not significantly hinder the effect of the present invention (for example, 10% by mass or less, 5% by mass or less, or 1% by mass or less relative to the total mass of the positive electrode active material).

[0029] In the first lithium composite oxide, the molar ratio of Li to metal (Me) other than Li (hereinafter also referred to as "Li / Me ratio") is 0.90 to 0.97. On the other hand, in the second lithium composite oxide, the molar ratio of Li to metal (Me) other than Li (Li / Me ratio) is 1.10 to 1.20.

[0030] Furthermore, the crystallite diameter of the (104) plane of the first lithium composite oxide is Furthermore, the crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.

[0031] In this way, by making the Li / Me ratio of the two lithium composite oxides within the above range and making the crystallite diameter of the (104) plane within the above range, the output characteristics and capacity characteristics of the lithium ion secondary battery 100 using the positive electrode 50 can be improved. The reasons are considered to be as follows. By obtaining a balance in the Li / Me ratio and limiting the crystallite diameter, when lithiation occurs in the lithium composite oxide (especially the first lithium composite oxide), the formation of an excess resistance layer (Li2CO3, LiOH) at the surface of the lithium composite oxide is suppressed, and the crystal structure is rearranged. These contribute to the improvement of the output characteristics and capacity characteristics.

[0032] Specifically, when the Li / Me ratio in the first lithium composite oxide is outside the range of 0.90 to 0.97, the capacity characteristics become insufficient. When the Li / Me ratio in the second lithium composite oxide is outside the range of 1.10 to 1.20, the capacity characteristics also become insufficient. From the perspective of increasing the capacity of the lithium ion secondary battery 100, the Li / Me ratio in the second lithium composite oxide is preferably 1.10 to 1.15, and more preferably 1.10 to 1.12.

[0033] The crystallite diameter on the (104) plane of the first lithium composite oxide is If the crystallite diameter of the first lithium composite oxide (104) plane is outside the range of More preferably More preferably

[0034] If the crystallite diameter of the (104) plane of the second lithium composite oxide is smaller than the crystallite diameter of the (104) plane of the first lithium composite oxide, the output characteristics become insufficient. The crystallite diameter of the (104) plane of the second lithium composite oxide is preferably larger than the crystallite diameter of the (104) plane of the first lithium composite oxide. More than, more preferably Above, further preferably Above, especially preferably The crystallite diameter of the (104) plane of the second lithium composite oxide is preferably More preferably

[0035] The Li / Me ratio and crystallite diameter of the lithium composite oxide can be adjusted according to a known method. For example, in general, the lithium composite oxide is manufactured by mixing and calcining a precursor (e.g., a hydroxide containing Me, a carbonate containing Me, etc.) containing a metal element (Me) other than Li with a Li source compound (e.g., lithium hydroxide, lithium carbonate, lithium chloride, etc.). Among them, the Li / Me ratio can be controlled by adjusting the mixing ratio of the precursor and the Li source compound. In addition, the crystallite diameter can be controlled by adjusting the calcining conditions. In particular, if the calcining temperature is increased, the crystallite diameter tends to become larger.

[0036] In addition, in a used lithium-ion secondary battery, the Li / Me ratio of the lithium composite oxide may decrease due to the release of Li. In addition, due to the expansion / contraction of the lithium composite oxide during the charge and discharge cycle, the crystallites are destroyed and sometimes the crystallites become smaller. Therefore, in a used lithium-ion secondary battery, a crystallite with a Li / Me ratio in the range of 0.90 to 0.97 and a (104) plane diameter of A layered lithium composite oxide within the range of.

[0037] Therefore, in the present embodiment, as the first lithium composite oxide, a layered lithium composite oxide recovered from a used lithium ion secondary battery can be used. In this case, it is advantageous from the viewpoint of reducing the environmental load. Furthermore, the lithium composite oxide can be recovered from a used lithium ion secondary battery by a known method. For example, by dismantling the used lithium ion secondary battery, taking out the positive electrode, peeling the positive electrode active material layer from the positive electrode collector, using a solvent, removing the binder, and separating the lithium composite oxide and the conductive material by classification, the lithium composite oxide can be obtained. On the other hand, the second lithium composite oxide can be a non-recoverable lithium composite oxide.

[0038] It should be noted that the crystallite diameter of the (104) plane of the lithium composite oxide can be obtained by X-ray diffraction (XRD) measurement of the lithium composite oxide powder. Specifically, using a known X-ray diffraction (XRD) device, the X-ray diffraction pattern is measured, and the half-peak full width (half-peak width) and 2θ value of the diffraction peak (2θ = 44 ± 1°) belonging to the (004) plane and the Scherrer formula can be used to calculate the crystallite diameter. In addition, in the case where the positive electrode already contains a positive electrode active material, only the positive electrode active material can be isolated according to a known method and used as a measurement sample.

[0039] When the first lithium composite oxide is a lithium nickel cobalt manganese composite oxide, the first lithium composite oxide has a composition represented by the following formula (I), for example.

[0040] Li x1 Ni y1 Coz1 Mn (1-y1-z1) M1 α1 O 2-β1 Q1 β1 (I)

[0041] In formula (I), x1, y1, z1, α1 and β1 satisfy 0.90≤x1≤0.97, 0<y1≤0.40, 0<z1≤0.40, 0≤α1≤0.10, 0≤β1≤0.5 respectively. M1 is at least one element selected from Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Sn, B and Al. Q1 is at least one element selected from F, Cl and Br.

[0042] y1 preferably satisfies 0.05≤y1≤0.40. z1 preferably satisfies 0.05≤z1≤0.40. α1 preferably satisfies 0≤α1≤0.05, and more preferably 0≤α1≤0.03. β1 preferably satisfies 0≤β1≤0.1, and more preferably 0.

[0043] When the second lithium composite oxide is a lithium nickel cobalt manganese-based composite oxide, the second lithium composite oxide has a composition represented by the following formula (II), for example.

[0044] Li x2 Ni y2 Co z2 Mn (1-y2-z2) M2 α2 O 2-β2 Q2 β2 (II)

[0045] In formula (II), x2, y2, z2, α2 and β2 satisfy 1.10≤x≤1.20, 0<y2≤0.40, 0<z2≤0.40, 0≤α2≤0.10, 0≤β2≤0.5 respectively. M2 is at least one element selected from Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Sn, B and Al. Q2 is at least one element selected from F, Cl and Br.

[0046] x2 preferably satisfies 1.10≤x2≤1.15, and more preferably satisfies 1.10≤x2≤1.12. y2 preferably satisfies 0.05≤y2≤0.40. z2 preferably satisfies 0.05≤z2≤0.40. α2 preferably satisfies 0≤α2≤0.05, and more preferably 0≤α2≤0.03. β2 preferably satisfies 0≤β2≤0.1, and more preferably 0.

[0047] The composition of the first lithium composite oxide and the composition of the second lithium composite oxide may be the same or different except for the Li / Me ratio.

[0048] When the composition of the first lithium composite oxide and the composition of the second lithium composite oxide are different, it is easy to distinguish the first lithium composite oxide from the second lithium composite oxide.

[0049] When the composition of the first lithium composite oxide is the same as that of the second lithium composite oxide except for the Li / Me ratio, it is easy to adjust the characteristics of the lithium ion secondary battery 100. In this case, for example, in the above formula (I) and the above formula (II), x1 and x2 are different, y1=y2, z1=z2, α1=α2, β1=β2, M1=M2, and Q1=Q2.

[0050] The average particle size (D50) of the first lithium composite oxide and the second lithium composite oxide is not particularly limited, for example, it is 0.05μm to 25μm. The average particle size (D50) of the first lithium composite oxide is preferably 1μm to 15μm, more preferably 2μm to 12μm, and further preferably 3μm to 8μm. When the average particle size (D50) of the first lithium composite oxide is 3μm to 8μm, the output characteristics of the lithium ion secondary battery become particularly high. The average particle size (D50) of the second lithium composite oxide is preferably 1μm to 15μm, more preferably 2μm to 12μm.

[0051] It should be noted that in this specification, "average particle size (D50)" means the particle size equivalent to 50 volume % of the cumulative frequency from the side of the particles with small particle size in the volume-based particle size distribution based on the laser diffraction scattering method. Therefore, the average particle size (D50) can be obtained using a known laser diffraction scattering type particle size distribution measuring device.

[0052] The mixing ratio of the first lithium composite oxide and the second lithium composite oxide is not particularly limited. The mass ratio of the first lithium composite oxide to the second lithium composite oxide is, for example, 5:95 to 95:5, preferably 10:90 to 90:10, more preferably 30:70 to 70:30, and further preferably 40:60 to 60:40.

[0053] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is preferably 87 mass % or more, more preferably 90 mass % or more, and further preferably 96 mass % or more.

[0054] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a conductive material, a binder, etc. As the conductive material, for example, carbon black such as acetylene black (AB); carbon nanotubes (CNT); other carbon materials (such as graphite, etc.) may be preferably used. As the binder, for example, polyvinylidene fluoride (PVdF) may be used. In addition, when CNT is used as the conductive material, the positive electrode active material layer 54 may contain a dispersant for CNT.

[0055] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 85% by mass or more and 99% by mass or less. There is no particular restriction on the content of trilithium phosphate in the positive electrode active material layer 54, preferably 0.1% by mass or more and 15% by mass or less, more preferably 0.2% by mass or more and 10% by mass or less. There is no particular restriction on the content of the conductive material in the positive electrode active material layer 54, preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.3% by mass or more and 15% by mass or less. There is no particular restriction on the content of the binder in the positive electrode active material layer 54, preferably 0.4% by mass or more and 15% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less.

[0056] The thickness per single side of the positive electrode active material layer 54 is not particularly limited, but is usually 10 μm or more, preferably 20 μm or more. On the other hand, the thickness is usually 300 μm or less, preferably 200 μm or less.

[0057] In the positive electrode active material layer non-forming portion 52a of the positive electrode 50, an insulating protective layer (not shown) containing insulating particles (e.g., ceramic particles) may be provided at a position adjacent to the positive electrode active material layer 54. This protective layer can prevent a short circuit between the positive electrode active material layer non-forming portion 52a and the negative electrode.

[0058] The positive electrode 50 involved in this embodiment can be manufactured by preparing a positive electrode slurry containing a positive electrode active material, any components (such as a binder, a conductive material, etc.) and a solvent (dispersion medium), applying the slurry on the positive electrode collector 52, drying it, and then performing a pressing process as needed.

[0059] According to the positive electrode 50 according to the present embodiment, it is possible to provide the secondary battery with both high-level capacity characteristics and high-level output characteristics.

[0060] Therefore, from another perspective, the secondary battery according to the present embodiment includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode is the positive electrode according to the present embodiment described above.

[0061] The secondary battery according to this embodiment is described in detail below by taking a flat rectangular lithium ion secondary battery having a flat wound electrode body and a flat battery case as an example. However, the secondary battery according to this embodiment is not limited to the example described below.

[0062] Figure 2 The lithium-ion secondary battery 100 shown is a sealed battery constructed by accommodating a flat wound electrode body 20 and a non-aqueous electrolyte 80 in a flat square battery case (i.e., outer packaging container) 30. The battery case 30 is provided with a positive terminal 42 and a negative terminal 44 for external connection, and a thin-walled safety valve 36 designed to release the internal pressure when the internal pressure of the battery case 30 rises to a specified level. In addition, the battery case 30 is provided with an injection port (not shown) for injecting the non-aqueous electrolyte 80. The positive terminal 42 is electrically connected to the positive electrode collector plate 42a. The negative terminal 44 is electrically connected to the negative electrode collector plate 44a. As the material of the battery case 30, a lightweight metal material with good thermal conductivity, such as aluminum, is used. It should be noted that, Figure 2 This does not accurately represent the amount of the nonaqueous electrolyte 80 .

[0063] The wound electrode body 20 is Figure 2 and Figure 3 As shown, the positive electrode sheet 50 and the negative electrode sheet 60 are stacked with two long separator sheets 70 interposed therebetween and then wound in the longitudinal direction.

[0064] The positive electrode 50 according to the present embodiment is used as the positive electrode sheet 50. The positive electrode sheet 50 has a structure in which a positive electrode active material layer 54 is formed on one side or both sides (here both sides) of a long strip of positive electrode collector 52 along the length direction. The negative electrode sheet 60 has a structure in which a negative electrode active material layer 64 is formed on one side or both sides (here both sides) of a long strip of negative electrode collector 62 along the length direction.

[0065] The positive electrode 50 has a positive electrode active material layer non-formed portion 52a where the positive electrode current collector 52 is exposed without forming the positive electrode active material layer 54. The negative electrode 60 has a negative electrode active material layer non-formed portion 62a where the negative electrode current collector 62 is exposed without forming the negative electrode active material layer 64. The positive electrode active material layer non-formed portion 52a and the negative electrode active material layer non-formed portion 62a are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction orthogonal to the above-mentioned longitudinal direction) of the wound electrode body 20. The positive electrode current collector plate 42a and the negative electrode current collector plate 44a are joined to the positive electrode active material layer non-formed portion 52a and the negative electrode active material layer non-formed portion 62a, respectively.

[0066] A known negative electrode collector used in lithium ion secondary batteries can be used as the negative electrode collector 62 constituting the negative electrode sheet 60, and examples thereof include sheets or foils made of metals with good conductivity (such as copper, nickel, titanium, stainless steel, etc.). The negative electrode collector 62 is preferably copper foil.

[0067] The size of the negative electrode current collector 62 is not particularly limited and can be appropriately determined according to the battery design. When copper foil is used as the negative electrode current collector 62, its thickness is not particularly limited, and is, for example, 5 μm to 35 μm, preferably 7 μm to 20 μm.

[0068] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, carbon materials such as graphite, hard carbon, and soft carbon; Si; and composite materials of Si and carbon can be used. The graphite can be natural graphite or artificial graphite, and the graphite can be amorphous carbon-coated graphite in the form of being coated with an amorphous carbon material.

[0069] The average particle size (D50) of the negative electrode active material is not particularly limited, and is, for example, 0.1 μm to 50 μm, preferably 1 μm to 25 μm, and more preferably 5 μm to 20 μm.

[0070] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), etc. can be used. As the thickener, for example, carboxymethyl cellulose (CMC) can be used.

[0071] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, more preferably 0.5% by mass or more and 2% by mass or less.

[0072] The thickness of the negative electrode active material layer 64 is not particularly limited, and is, for example, 10 μm or more and 300 μm or less, and preferably 20 μm or more and 200 μm or less.

[0073] As the separator 70, for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) can be provided on the surface of the separator 70.

[0074] The non-aqueous electrolyte 80 typically contains a non-aqueous solvent and a supporting salt (electrolyte salt). As a non-aqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, lactones used in the electrolyte of a general lithium ion secondary battery can be used without particular limitation. As a specific example, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), etc. can be illustrated. Such a non-aqueous solvent can be used alone, or two or more can be used in combination as appropriate.

[0075] As the supporting salt, for example, lithium salts such as LiPF6, LiBF4, and lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be appropriately used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0076] Furthermore, the above-mentioned non-aqueous electrolyte 80 may contain components other than the above-mentioned components, such as film forming agents such as vinylene carbonate (VC) and oxalic acid complex; gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and various additives such as thickeners, as long as the effects of the present invention are not significantly impaired.

[0077] The lithium ion secondary battery 100 configured as described above is excellent in both capacity characteristics and output characteristics. That is, the lithium ion secondary battery 100 has high capacity and high output.

[0078] The lithium-ion secondary battery 100 can be used in various applications. Specific applications include portable power sources for personal computers, portable electronic devices, portable terminals, etc.; vehicle driving power sources such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); batteries for small power storage devices, etc., among which vehicle driving power sources are preferred. The lithium-ion secondary battery 100 can also be typically used in the form of a battery pack formed by connecting a plurality of batteries in series and / or in parallel.

[0079] Furthermore, as an example, a square lithium-ion secondary battery 100 including a flat wound electrode body 20 is described. However, the lithium-ion secondary battery disclosed herein can also be configured as a lithium-ion secondary battery including a stacked electrode body (i.e., an electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked). In addition, the nonaqueous electrolyte secondary battery disclosed herein can also be configured as a cylindrical lithium-ion secondary battery, a stacked shell lithium-ion secondary battery, a coin-shaped lithium-ion secondary battery, etc.

[0080] In addition, according to a known method, using the above-mentioned positive electrode, a secondary battery other than a lithium ion secondary battery can also be constructed. Furthermore, according to a known method, using a solid electrolyte instead of the non-aqueous electrolyte 80 can construct an all-solid secondary battery (especially an all-solid lithium ion secondary battery).

[0081] The following describes embodiments related to the present invention, but the present invention is not intended to be limited to the contents shown in these embodiments.

[0082] <Examples 1 to 14 and Comparative Examples 1 to 5>

[0083] As a precursor of the positive electrode active material, Ni 1 / 3 Co 1 / 3 Mn 1 / 3 Nickel-cobalt-manganese composite hydroxide represented by (OH)2.

[0084] The first lithium composite oxide is prepared by the following steps. First, the prepared composite hydroxide and lithium source (lithium carbonate) are mixed in a manner to obtain the Li / Me ratio shown in Tables 1 and 2. It is sintered at the temperature shown in Tables 1 and 2 for 12 hours to obtain the first lithium composite oxide (lithium nickel cobalt manganese composite oxide). In addition, in Examples 7, 13 and 14, a composite hydroxide with an average particle size (D50) of 7 μm is used, in Examples 9 and 10, a composite hydroxide with an average particle size (D50) of 3 μm is used, in Example 11, a composite hydroxide with an average particle size (D50) of 2 μm is used, in Example 12, a composite hydroxide with an average particle size (D50) of 11 μm is used, and in other examples and comparative examples, a composite hydroxide with an average particle size (D50) of 9 μm is used. The value of the average particle size (D50) of the first lithium composite oxide measured using a commercially available laser diffraction scattering particle size distribution measuring device is shown in Tables 1 and 2.

[0085] The second lithium composite oxide is prepared by the following steps. First, the above-mentioned composite hydroxide and lithium source (lithium carbonate) are mixed in a manner to obtain the Li / Me ratio shown in Tables 1 and 2. It is sintered at the temperature shown in Tables 1 and 2 for 12 hours to obtain a second lithium composite oxide (lithium nickel cobalt manganese composite oxide). Furthermore, in Example 8, a composite hydroxide with an average particle size (D50) of 7 μm is used, in Example 13, a composite hydroxide with an average particle size (D50) of 3 μm is used, and in Example 14, a composite hydroxide with an average particle size (D50) of 11 μm is used. In other examples and comparative examples, a composite hydroxide with an average particle size (D50) of 9 μm is used. The value of the average particle size (D50) of the second lithium composite oxide measured using a commercially available laser diffraction scattering particle size distribution measuring device is shown in Tables 1 and 2.

[0086] The prepared first lithium composite oxide and the second lithium composite oxide were mixed at the mass ratio shown in Table 1 and Table 2 to obtain a positive electrode active material.

[0087] The obtained positive electrode active material, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder were mixed in N-methylpyrrolidone (NMP) at a mass ratio of positive electrode active material: AB: PVDF = 85:10:5 to prepare a paste for forming a positive electrode active material layer. The paste was applied on an aluminum foil with a thickness of 15 μm and dried to prepare a positive electrode sheet.

[0088] Natural graphite (C) as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed in ion exchange water at a mass ratio of C:SBR:CMC = 98:1:1 to prepare a paste for forming a negative electrode active material layer. The paste was applied on a copper foil with a thickness of 10 μm and dried to prepare a negative electrode sheet.

[0089] In addition, as a separator sheet, a porous polyolefin sheet having a three-layer structure of PP / PE / PP and a thickness of 20 μm was prepared.

[0090] The positive electrode sheet, negative electrode sheet and separator sheet are overlapped, the electrode terminals are installed, and the laminated shell is contained. Next, a non-aqueous electrolyte is injected into the laminated shell, and the laminated shell is hermetically sealed. In addition, for the non-aqueous electrolyte, a non-aqueous electrolyte is used in which LiPF6 as a supporting salt is dissolved at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3. As described above, a lithium-ion secondary battery for evaluation of each embodiment and each comparative example is obtained.

[0091] <Measurement of crystallite diameter>

[0092] The first lithium composite oxide and the second lithium composite oxide prepared above were analyzed using an XRD device "smart Lab" (manufactured by Rigaku) ​​and an analysis software "PDXL2" (manufactured by Rigaku), respectively, and the crystallite diameter was obtained using the half-maximum full width, 2θ value and Scherrer formula of the diffraction peak (2θ=44±1°) belonging to the (004) plane. The results are shown in Tables 1 and 2.

[0093] <Activation and initial capacity measurement>

[0094] Each of the evaluation lithium-ion secondary batteries prepared above was placed in an environment of 25°C. Activation (initial charge) was performed in a constant current-constant voltage mode. Each evaluation lithium-ion secondary battery was charged with a constant current at a current value of 1 / 3C until it reached 4.2V, and then charged with a constant voltage until the current value reached 1 / 50C, so that it was fully charged. Then, each evaluation lithium-ion secondary battery was discharged with a current value of 1 / 3C at a constant current until it reached 3.0V. Then, the discharge capacity at this time was measured to determine the initial capacity. Calculate the ratio of the initial capacity of other comparative examples and embodiments when the initial capacity of comparative example 1 is set to 1. The results are shown in Tables 1 and 2.

[0095] <Output Characteristics Evaluation>

[0096] After activation treatment, each evaluation lithium ion secondary battery was adjusted to SOC 60% and placed in an environment of -10°C. For each evaluation lithium ion secondary battery, discharge was performed for 2 seconds with a current value of 15C. Based on the voltage and current value at this time, the output (W) was calculated. The ratio of the output of the evaluation lithium ion secondary battery using the positive electrode active material obtained in Comparative Example 1 to the output of the evaluation lithium ion secondary battery using the positive electrode active material obtained in other comparative examples and embodiments was calculated. The results are shown in Tables 1 and 2.

[0097] [Table 1]

[0098]

[0099] [Table 2]

[0100]

[0101] From the results in Tables 1 and 2, it can be seen that the Li / Me ratio in the first lithium composite oxide is 0.90 to 0.97, the Li / Me ratio in the second lithium composite oxide is 1.10 to 1.20, and the crystallite diameter of the (104) plane of the first lithium composite oxide is When the crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide, both the capacity and the output are improved.

[0102] Therefore, it can be seen that the positive electrode disclosed herein can provide a secondary battery with both high-level capacity characteristics and high-level output characteristics.

[0103] The specific examples of the present invention have been described in detail above, but these are merely examples and do not limit the claims. The technology described in the claims includes various modifications and changes of the specific examples described above.

[0104] That is, the positive electrode and the secondary battery disclosed herein are the following items [1] to [6].

[0105] [1] A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported by the positive electrode current collector, wherein the positive electrode active material layer contains: a first lithium composite oxide having a layered structure, and a second lithium composite oxide having a layered structure, wherein the molar ratio of Li to metal other than Li in the first lithium composite oxide is 0.90 to 0.97, and the molar ratio of Li to metal other than Li in the second lithium composite oxide is 1.10 to 1.20, and the crystallite diameter of the (104) plane of the first lithium composite oxide is The crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.

[0106] [2] The positive electrode according to item [1], wherein the crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide. and the crystallite diameter of the (104) plane of the second lithium composite oxide is

[0107] [3] The positive electrode according to item [1] or [2], wherein the first lithium composite oxide and the second lithium composite oxide are both lithium nickel cobalt manganese-based composite oxides.

[0108] [4] The positive electrode according to any one of items [1] to [3], wherein the first lithium composite oxide is a lithium composite oxide recovered from a used lithium ion secondary battery.

[0109] [5] The positive electrode according to any one of items [1] to [4], wherein an average particle size (D50) of the first lithium composite oxide is 3 μm to 8 μm.

[0110] [6] A secondary battery comprising: the positive electrode according to any one of items [1] to [5], a negative electrode, and an electrolyte.

Claims

1. A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported by the positive electrode current collector, wherein: The positive electrode active material layer comprises: a first lithium composite oxide having a layered structure, and a second lithium composite oxide having a layered structure, wherein the molar ratio of Li to metal other than Li in the first lithium composite oxide is 0.90 to 0.97, and the molar ratio of Li to metal other than Li in the second lithium composite oxide is 1.10 to 1.20, and the crystallite diameter of the (104) plane of the first lithium composite oxide is The crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.

2. The positive electrode according to claim 1, wherein The crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide. and the crystallite diameter of the (104) plane of the second lithium composite oxide is 3. The positive electrode according to claim 1, wherein The first lithium composite oxide and the second lithium composite oxide are both lithium nickel cobalt manganese composite oxides.

4. The positive electrode according to claim 1, wherein The first lithium composite oxide is a lithium composite oxide recovered from a used lithium ion secondary battery.

5. The positive electrode according to claim 1, wherein The average particle size (D50) of the first lithium composite oxide is 3 μm to 8 μm.

6. A secondary battery comprising: The positive electrode, negative electrode, and electrolyte according to claim 1.

Citation Information

Patent Citations

  • Cathode material for lithium secondary battery, cathode for lithium secondary battery including the same, and lithium secondary battery

    JP2021518049A